Characteristics and health effect of heavy metals on non-exhaust road dusts in Kuala Lumpur - Wahab, Muhammad Ikram A.; Razak, Wan Mohd Amirfaqry Abd; Sahani, Mazrura; Khan, Md Firoz (Elsevier, 2020)
This study aimed to assess the concentrations and health effect of trace metals [cadmium (Cd), chromium (Cr), copper (Cu), lead (Pb), nickel (Ni), and zinc (Zn)] on the road dust of selected locations in the city of Kuala Lumpur. Sampling was conducted thrice at four locations, namely, Tun Razak Road, Raja Abdullah Road, Tunku Abdul Rahman (TAR) Road, and Ayer Molek Road. The concentrations of trace metals in road dust were analyzed by inductively coupled plasma mass spectrometry. TAR Road presented the highest Cd, Cu, Ni, and Pb contents compared with the other roads. The pollution level of trace metals in road dust was assessed by pollution index and pollution load index (PLI), showing that all studied locations were highly contaminated except Ayer Molek Road. Based on the PLI value, the sequence of pollution in descending order is as follows: TAR Road > Raja Abdullah Road > Tun Razak Road > Ayer Molek Road. Health risk assessment was performed to assess the health effects of carcinogenic and noncarcinogenic pollutants caused by the exposure to trace metals in road dust on adults and children. Based on the integrated hazard index values for children at all locations, >1 indicates a possible noncarcinogenic effect. All incremental lifetime cancer risk values for adult and children at all locations are within acceptable limits and are considered safe. © 2019